Isolation and isoenzyme characterization of Leishmania (Viannia) braziliensis from a case of human cutaneous leishmaniasis in northeast centre of the state of São Paulo - Pinto, MC [UNESP]; Rosa, JA da [UNESP]; Fernandes, ZMT [UNESP]; Graminha, MAS [UNESP]; Mine, JC [UNESP]; Allegretti, SM; Delort, S; Riedel, C; Paes, EL; Cupolillo, E (Instituto Oswaldo Cruz, Ministério da Saúde, 2005)
The diagnosis of human cutaneous leishmaniasis in small towns is sometimes made without the species identification of the Leishmania, even in areas without previous epidemiological surveys. Here we report the isolation of a Leishmania strain from a patient of Rincão, state of São Paulo, that was identified by isoenzyme characterization as L. (Viannia) braziliensis. Sand fly collections were made in the area where the patient live in order to investigate the likely vector species.
Keywords: Leishmania braziliensis; isolation; Brazil